Modeling and simulation of a multistage heat recovery steam generator. (February 2023) - McConnell, Jonathan; Das, Tuhin; Caesar, Andres; Veeravalli, Prithvi
As the share of renewable energy increases in modern power grids, their inherent intermittency compels existing thermal power plants to become more agile and flexible in their operation. To achieve such flexibility, understanding the transient behavior of thermal power plants is key. In this regard, physics-based dynamic models are useful tools. They help in predicting performance and in exploring various operating conditions in a risk-free, cost-effective manner. To this end, this paper presents a multi-stage Heat Recovery Steam Generator (HRSG) model. Fast simulations are demonstrated for this three pressure-stage system with interconnected thermodynamic and mass transfer phenomena. The HRSG's multi-physics behavior is captured through mathematically modeled and numerically simulated phase change, fluid dynamics, and thermal coupling. Heat exchange elements such as economizers and superheaters are modeled by directly solving the Unsteady Flow Energy Equation (UFEE). The phase change dynamics of the boiler are modeled using a multi-mode switching mechanism, where each mode is characterized by boiling/evaporation/condensation and heating/cooling phenomena. A judicious combination of spatially discretized or lumped and dynamic or quasi-static models is used to achieve reasonably accurate transient response while lowering the computational burden. In collaboration with Siemens Energy Inc., steady-state prediction capability and transient pressure behavior are validated with plant startup data from an operational HRSG.